2018
DOI: 10.1016/j.jveb.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Hauliers' perceptions and attitudes towards farm animal welfare could influence the operational and logistics practices in sheep transport

Abstract: A survey of Mexico-based sheep hauliers was conducted in order to investigate perceptions and attitudes toward farm animal welfare (FAW) and their influence on operational and logistic practices (OLPs) in sheep transportation. The statistical analysis consisted in the application of 2-factor analyses (OLP and animal welfare attitudes), additionally a cluster analysis; the latter allowed a segmentation of hauliers according to their attitudes and OLP. The factor analysis gave 3 OLP factors: logistic issues, eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…In our study, handlers that generally had positive attitude and empathy scores were associated with a significant decrease in the number of negative tactile interactions, such as prodding and shouting; results that coincided with those reported by other researchers in studies on dairy farms [36,37] and extensive beef cattle systems [8]. Likewise, a study evaluating the attitudes of Japanese workers toward cows found that handlers with high positive attitude scores had a greater tendency to exhibit more positive tactile behavior (e.g., petting), and less to encourage and implement effective methods for improving attitudes, such as providing livestock handlers with new information, creating stimuli, constantly reinforcing the need to treat the animals well [8,38], and promoting actions that increase job satisfaction [39], among others.…”
Section: Relationships Between Attitude Empathy and Human-animal Intmentioning
confidence: 99%
“…In our study, handlers that generally had positive attitude and empathy scores were associated with a significant decrease in the number of negative tactile interactions, such as prodding and shouting; results that coincided with those reported by other researchers in studies on dairy farms [36,37] and extensive beef cattle systems [8]. Likewise, a study evaluating the attitudes of Japanese workers toward cows found that handlers with high positive attitude scores had a greater tendency to exhibit more positive tactile behavior (e.g., petting), and less to encourage and implement effective methods for improving attitudes, such as providing livestock handlers with new information, creating stimuli, constantly reinforcing the need to treat the animals well [8,38], and promoting actions that increase job satisfaction [39], among others.…”
Section: Relationships Between Attitude Empathy and Human-animal Intmentioning
confidence: 99%
“…Safe and humane livestock transportation carries important public and trade concerns worldwide because of its potential negative consequences on economics, animal health and welfare, food quality, and safety (González et al, 2012). Transporters play a crucial role in delivering live and healthy animals to their destinations on time, despite long journeys and irregular driving schedules (Pulido et al, 2018). Surprisingly, we know little about how transporters influence animal welfare.…”
Section: Discussionmentioning
confidence: 99%
“…The survey period was from May to September 2016. The first article in this series study the transporters perceptions and attitudes toward animal welfare and their influence in logistics practices in sheep transport (see Pulido et al, 2018), and this article integrates the knowledge of transporters about Mexican preslaughter logistic chain and occupational risks and its impact on sheep welfare. In Mexico, sheep are slaughtered, and meat is processed in the central area of the country, mostly because of the high demand in Hidalgo and Mexico City where sheep meat is consumed as a traditional dish called "barbacoa".…”
Section: Methodsmentioning
confidence: 99%
“…Experience, skills and stock handler skills are likely to vary greatly between sectors of the LEI supply chain, while there are also different attitudes towards livestock handling across the globe [ 46 , 47 , 48 ]. The staff and the time available to carry out animal welfare assessments will therefore vary across the chain and needs to be considered when designing protocols.…”
Section: Constraints On Animal Welfare Assessmentsmentioning
confidence: 99%